Penyuluhan Perilaku Hidup Bersih dan Sehat (PHBS) Pada Siswa Sekolah Dasar - Erni Susanty Tahir; Fatika Puteri Rosyi; Puput Mulyono (Jurnal Pelayanan Masyarakat, 2025)
Schools serve as environments where children receive a formal education. In addition to serving as educational institutions, schools can also pose a risk for spreading diseases. Diarrhea accounts for up to 65% of deaths, while other illnesses contribute to 26%. Healthy and clean living practices involve initiatives to offer learning experiences or establish environments for individuals, families, groups, and communities by facilitating communication, sharing information, and arranging educational opportunities to enhance knowledge, attitudes, and actions. This community service seeks to impart knowledge and awareness of clean and healthy living habits to Sekolah Dsar children, enabling them to incorporate these practices into their everyday lives. This community service is conducted through counseling delivered via lectures, interactive discussions, and simulations utilizing LCD media and instructional materials. The event was successful, and everyone involved was excited about this service project.